ANALISIS HASIL INVESTIGASI KECELAKAAN KERJA PADA INALUM SMELTING PLANT (ISP) PT INDONESIA ASAHAN ALUMINIUM KUALA TANJUNG TAHUN 2014 - aprilia rizki ardila; halinda sari lubis; eka lestari lubis (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Occupational accident is work-related event that could cause injury or illness and even death. In the cycle of accident prevention, one of the important thing is how to conduct the accident investigation to find the factors that caused the accident. Accident investigation is essential to design prevention programs so the same accident will not happen again. Human Factors Analysis and Classification System (HFACS) is a method of occupational accidents analysis with a systematic approach to determine the main cause of the accidents. This study was a descriptive study in which the author tried to analyze the occupational accident investigation in Inalum Smelting Plant (ISP) PT Inalum 2014 using HFACS. The data that being used are secondary data from the accident investigation report of PT Inalum 2014. The results showed that the Performance-based error is the greatest type of error that causes unsafe actions that was 45%. Judgment and decision-making error was in the second place with 33% and violation was 22%. Mental awareness (physical readiness) and technological environment are precondition that provides the greatest contribution to the work accident, that was 25%. State of mind and physical environment was 19%. Teamwork also has contribution of the occupational accident as many 12%. Inadequate supervision and planned inappropriate operation have contributed 37.5% of the accidents that occur. While supervisory violations has contributed 25% of the accidents that occur. Policy and proess issues have contributed 56% and climate/culture influences has contributed 43% of the accident that occurred in Inalum Smelting Plant. Based on the results of the study, PT Inalum Kuala Tanjung is expected to give and improve education, training, and guidance about occupational health and safety especially in abnormal condition so the laborer can decide the right act while working and establish communication between employees and group/units effectively. Keywords : Occupational accident, Accident investigation, HFACS